2019
DOI: 10.1242/jeb.212787
|View full text |Cite
|
Sign up to set email alerts
|

Stepping behavior contributes little to balance control against continuous mediolateral trunk perturbations

Abstract: Human bipedal gait is exceptionally stable, but the underlying strategies to maintain stability are unclear, especially in the frontal plane. Our study investigates balance strategies of healthy adults subjected to continuous mediolateral oscillations at the trunk during walking. We used a backpack with a passive inverted pendulum to create perturbations that were fixed, in-phase, or out-of-phase with subjects’ trunk. We evaluated subjects’ corrective strategies and whether they yielded equivalent stability, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…The possible distinction between error-based adaptation and reinforcement learning is currently speculative, and carefully designed future work will be required to differentiate between these mechanisms. Additionally, our finding that perturbations influence the active control of step width may be specific to perturbations that target the legs, as recent work has reported that mediolateral trunk perturbations have a more notable effect on control of the trunk 41 .…”
Section: Discussionmentioning
confidence: 54%
“…The possible distinction between error-based adaptation and reinforcement learning is currently speculative, and carefully designed future work will be required to differentiate between these mechanisms. Additionally, our finding that perturbations influence the active control of step width may be specific to perturbations that target the legs, as recent work has reported that mediolateral trunk perturbations have a more notable effect on control of the trunk 41 .…”
Section: Discussionmentioning
confidence: 54%
“…One device applied vibrations to the hip abductor muscles [ 39 ]. One study used an oscillating pendulum system worn on participants’ backs [ 40 ], one study applied a mechanised block to the foot [ 41 ], and one study applied a narrow treadmill-based stepping task while participants were executing a cognitive task [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Timing of balance perturbation onset : Fourteen studies initiated balance perturbations at heel strike [ 7 , 18 , 19 , 20 , 21 , 22 , 23 , 26 , 27 , 28 , 29 , 35 , 37 , 43 ]. Six studies applied balance perturbations continuously or at intervals during a walking trial [ 8 , 9 , 30 , 31 , 40 , 42 ]. Two studies perturbed participants at toe-off [ 25 , 36 ], one study during mid-stance [ 45 ], one study during single or double support [ 33 ], and one study prior to toe-off [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The trunk accounts for 48% of the body mass and is the largest contributor to the CoM (MacKinnon and Winter, 1993;Prince et al, 1994). Therefore, how the trunk is controlled will directly influence the CoM, and in some cases adjustment of the CoM motion is preferred over modifying foot placement (Best et al, 2019). The trunk should not be considered a rigid body, since structurally it involves multiple linked segments and degrees of freedom that needs to be fine-tuned.…”
Section: Introductionmentioning
confidence: 99%